2010
DOI: 10.1097/mph.0b013e3181cf444c
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Human Erythropoietin in the Prevention of Late Anemia in Intrauterine Transfused Neonates With Rh-isoimmunization

Abstract: The majority of neonates with Rh-isoimmunization develops late anemia between the second and the sixth week of life. We report the effectiveness of recombinant human erythropoietin (rHuEPO) in preventing late anemia in 25 intrauterine and nonintrauterine-transfused neonates. The neonates were treated from 11+/-4 days after birth to 26+/-14 days (400 U/kg/d of rHuEpo, administered subcutaneously). During rHuEpo therapy, vitamin E, calcium folinate, and iron maltose were administered intramuscularly on a daily b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…In accord with the results of a previous study [22], hypo generative late anemia in our cohort was significantly correlated with the need for more than 2 IUTs. Several previous studies [23][24][25] have reported that the use of IVIG with alloimmunization decreases the duration of hospitalization, the need for ET, and the need for phototherapy However; other recent studies (high quality RCT) have shown that the use of IVIG has no effect on the rate of ET.…”
Section: (33)supporting
confidence: 82%
See 1 more Smart Citation
“…In accord with the results of a previous study [22], hypo generative late anemia in our cohort was significantly correlated with the need for more than 2 IUTs. Several previous studies [23][24][25] have reported that the use of IVIG with alloimmunization decreases the duration of hospitalization, the need for ET, and the need for phototherapy However; other recent studies (high quality RCT) have shown that the use of IVIG has no effect on the rate of ET.…”
Section: (33)supporting
confidence: 82%
“…We would like to stress, however, that the use of high-dose IVIG was recently recommended to be used cautiously due to an increased incidence of NEC [29], which we did not note in our group of patients. This indicates the need to investigate the role of other alternative modalities, including intensive phototherapy, limited use of IVIG, and recombinant human erythropoietin [22]. The reported rate of Neurodevelopmental impairment is higher compared to a recent large cohort study [6].…”
Section: (33)mentioning
confidence: 58%
“…EPO is the principle growth factor responsible for fetal and neonatal erythropoiesis and is primarily developed in the fetal liver [70], since over a decade, recombinant human EPO has been applied in small studies and casuistic reports, with different outcomes for the occurrence of anemia and the need for top-up transfusions in neonates with HDFN [71][72][73][74]. Due to limited clinical importance of observed beneficial effects, routine use of EPO is currently not recommended [75].…”
Section: Epomentioning
confidence: 99%
“…8 Low erythropoietin production by the infant may also be contributory to low hemoglobin levels. 9 Late hemolysis can continue to cause low blood counts and elevated bilirubin.…”
Section: Epidemiology and Pathophysiologymentioning
confidence: 99%